Developmental temperature predicts body size, flight, and pollen load in a widespread butterfly. (17th June 2022) - Büyükyilmaz, Erez; Tseng, Michelle
Abstract: Most of our understanding of the effects of climate warming on insect body size comes from laboratory experiments. Whether these studies predict patterns in nature is largely unknown. Here we examine the relevance of laboratory warming experiments for wild populations of the butterfly Pieris rapae . We tested two predictions: (i) butterflies reared at warmer temperatures in the laboratory should attain smaller adult sizes and have reduced flight ability, and (ii) in nature, this trait combination should lead to smaller butterflies visiting fewer flowers and accumulating less pollen. Overall, we found that warm‐reared butterflies were indeed smaller and flew more slowly compared to colder‐reared conspecifics. Additionally, wild‐caught small butterflies carried fewer, and a lower diversity of pollen grains compared to larger butterflies. Our warming experiments thus largely predicted pollen collection patterns in wild P. rapae . This study demonstrates that increased temperatures will likely have important consequences for butterfly‐plant interactions in nature. Abstract : Here we used a laboratory experiment to demonstrate that warmer rearing temperatures reduced body size and fight speed in the widespread butterfly Pieris rapae . We also found that in nature, P. rapae of equivalent size to those reared in warmed laboratory conditions carried less pollen and visited fewer flower types compared to larger‐sized butterflies. Our study suggests that insect body size changes due to ongoing warming will have important effects on plant–pollinator interactions.